ANALYSIS OF THE EFFECT OF THE MARKETING MIX ON PURCHASING DECISIONS - Muhammad Yusuf; Nuuridha Matiin (Pusat Riset dan Inovasi Nasional, 2022)
Tea Powder is a delicious beverage powder in Bandung. In developing the business, the company will expand the sales area in each sub-district. The company chooses the low end segment, which is considered to be at low cost, and determines product positioning only in the sweet bread market. Management has conducted the marketing mix strategy. But, the effectiveness is still being debated, especially regarding the problems of the expansion of sales area. Thus, the scientifically conducted study is needed to measure the marketing mix and its influence on the decision, statistics, and the loyalty of customers. The results of the study showed that the overall hypothesis was acceptable and there were significant influences of the product, distribution and promotion on consumers' decisions; there were significant influences of product and price on consumers' satisfaction; there were significant influences of consumers' decision on consumers' satisfaction and loyalty, and there was a significant influence of consumers' satisfaction on consumers' loyalty.